Clinical and radiologic outcomes following resection of primary proximal fibula tumors: Proximal fibula resection outcomes. (25th March 2019) - Arikan, Yavuz; Misir, Abdulhamit; Gur, Volkan; Kizkapan, Turan Bilge; Dincel, Yasar Mahsut; Akman, Yunus Emre
Purpose: Reconstruction of the lateral collateral ligament (LCL) and biceps femoris tendon following proximal fibula resection is controversial. Postoperative knee instability and peroneal nerve dysfunction affect outcome. This study aimed to determine functional, clinical, and radiological outcomes of patients who underwent en bloc proximal fibula resections and to compare clinical and radiological instability rates for primary repair after type I and type II resections. Materials and Methods: Eleven patients with primary tumors of the proximal fibula were included. Musculoskeletal Tumor Society (MSTS) score and Lysholm knee score were used in the evaluation of functional outcomes. Clinical outcome was assessed using knee range of motion and knee varus stress test. Radiological outcome was assessed using varus stress knee radiographs. Knee stability was evaluated using the varus stress test at 30° of knee flexion and varus stress knee radiographs and graded in millimeters. Results: Of the 11 tumors, 6 (54.6%) underwent type I resection. In five (45.4%) patients, type II resection was performed. The mean follow-up period was 32 ± 13.9 months (range, 12–55 months; median, 27 months). The mean knee joint lateral opening, MSTS score, and Lysholm knee score with type I versus type II resection were 5.7 ± 1.2 mm versus 6.4 ± 1.1 mm ( p = 0.247), 28.7 ± 1.8 (95.6%) versus 20.4 ± 7.7 (68%) ( p = 0.011), and 92.2 ± 8.8 versus 62.8 ± 20.4 ( p = 0.026), respectively. Postoperative complications of all patients included one (9.1%) deep tissue infection and one (9.1%) long-term knee instability. In one patient (9.1%) who underwent type II resection, above-the-knee amputation was performed after local recurrence. Conclusions: Primary repair of the LCL and biceps femoris tendon to the surrounding soft tissues after resection of proximal fibular tumors provides good clinical outcomes. Primary repair is a simple technique to perform with minimal morbidity. Peroneal nerve palsy was a problem, especially in type II resections. Level of Evidence: Therapeutic Level III.